2018
DOI: 10.3390/ijms19092742
|View full text |Cite
|
Sign up to set email alerts
|

Concatenation of Human Connexin26 (hCx26) and Human Connexin46 (hCx46) for the Analysis of Heteromeric Gap Junction Hemichannels and Heterotypic Gap Junction Channels

Abstract: Gap junction channels and hemichannels formed by concatenated connexins were analyzed. Monomeric (hCx26, hCx46), homodimeric (hCx46-hCx46, hCx26-hCx26), and heterodimeric (hCx26-hCx46, hCx46-hCx26) constructs, coupled to GFP, were expressed in HeLa cells. Confocal microscopy showed that the tandems formed gap junction plaques with a reduced plaque area compared to monomeric hCx26 or hCx46. Dye transfer experiments showed that concatenation allows metabolic transfer. Expressed in Xenopus oocytes, the inside-out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In order to analyse the functionality of the Cx hemichannels formed in the membranes of transfected cells, we performed dye-uptake experiments [ 11 , 34 , 35 , 36 ]. The functionality of the Cx hemichannels was recognised as an accelerated increase in fluorescence intensity of the dye ethidium bromide (Etd) in the cells in response to the removal of external Ca 2+ , as compared to control conditions with 2 mM external Ca 2+ ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…In order to analyse the functionality of the Cx hemichannels formed in the membranes of transfected cells, we performed dye-uptake experiments [ 11 , 34 , 35 , 36 ]. The functionality of the Cx hemichannels was recognised as an accelerated increase in fluorescence intensity of the dye ethidium bromide (Etd) in the cells in response to the removal of external Ca 2+ , as compared to control conditions with 2 mM external Ca 2+ ( Figure 2 a).…”
Section: Resultsmentioning
confidence: 99%
“…We found that most parasites exhibited only a single homolog, except T. cruzi , T. brucei , and T. rangeli , which possessed five, three, and two, respectively. The expression of two or more homologs could allow the formation of heteromeric channels formed by different subunits as occurs in mammals with Cx26/Cx30 (Naulin et al, 2020), Cx26/Cx46 (Schadzek et al, 2018), Cx43/Cx46 (Hoang et al, 2010) hemichannels among others.…”
Section: Discussionmentioning
confidence: 99%
“…In order to analyse the functionality of the formed Cx hemichannels in the membrane of transfected cells, we performed dye uptake experiments [11], [34], [35], [36]. The functionality of Cx hemichannels was recognized as an accelerated increase of fluorescence intensity of the dye ethidium bromide (Etd) in the cells in response to the removal of external Ca 2+ as compared to control conditions with 2 mM external Ca 2+ (Figure 2a).…”
Section: Functionality Of Expressed CX Hemichannelsmentioning
confidence: 99%
“…For this work the expression vectors pEF1a B1-hCx26-B2-IRES-GFP, pEF1a B1-hCx46-B2-IRES-GFP [34], [60] were used and constructed by gateway cloning. The gene for human connexin (hCx) isoforms hCx26 or hCx46 were cloned in the vector pEF1a which has an IRES element between the gateway cassette and the reporter GFP.…”
Section: Molecular Cloning and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation